2023
DOI: 10.1007/s11356-023-26604-2
|View full text |Cite
|
Sign up to set email alerts
|

Haemato-biochemical, mutagenic, and histopathological changes in Oreochromis niloticus exposed to BTX

Abstract: The study of the DNA damage response in erythrocytes after exposure to volatile organic compounds (VOCs) can present evidence for its potential effect as genotoxic- biomarkers for environmental pollution. Although VOCs are dangerous pollutants, still little is known about hemotoxic, cytotoxic, and genotoxic effects of such pollutants on fish. We optimized an assay method for apoptosis and DNA damage in erythrocytes of adult tilapia fish after 15 days exposure to benzene (0.762 ng/L), toluene (26.614 ng/L), and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 76 publications
1
1
0
Order By: Relevance
“…The histopathological abnormalities in the liver and kidney of exposed groups are in the same line with those reported in the studies of Sayed et al 7 , 8 . As a consequence of loss of antioxidant defensive shield to fight damaging free radicals and increase in death-mediated proteoses 52 , 53 , and following the observations of Sayed et al 7 , 54 , our results revealed presence of necrotic alterations in the liver of benzene group and epithelial sloughing in the kidney of benzene and toluene groups. Loss of hepatocellular integrity is associated with the release of its metabolizing enzymes into the bloodstream 40 .…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The histopathological abnormalities in the liver and kidney of exposed groups are in the same line with those reported in the studies of Sayed et al 7 , 8 . As a consequence of loss of antioxidant defensive shield to fight damaging free radicals and increase in death-mediated proteoses 52 , 53 , and following the observations of Sayed et al 7 , 54 , our results revealed presence of necrotic alterations in the liver of benzene group and epithelial sloughing in the kidney of benzene and toluene groups. Loss of hepatocellular integrity is associated with the release of its metabolizing enzymes into the bloodstream 40 .…”
Section: Discussionsupporting
confidence: 90%
“…The quantities of benzene and toluene administered were determined through field studies conducted to investigate residues of commonly used products along the Nile River in four cities within the Assiut governorate 9 . The rationale behind choosing these doses was their capacity to induce disturbances in the redox equilibrium and trigger histopathological alterations in the liver and kidneys Sayed et al 7 . The fourth and fifth groups (SP + benzene and SP + toluene, respectively) were intoxicated with benzene and toluene as previously mentioned following the dietary addition of SP at a dose of 5 g/kg diet for 30 days.…”
Section: Methodsmentioning
confidence: 99%